Exegese, corporeidade e mortalidade no Leviatã de Thomas Hobbes - Santana, Luiz Felipe Sousa (Universidade Federal de São Carlos, 2021)
On his attempt to set up the principle for a science of civil or political bodies in Leviathan (1651), Thomas Hobbes (1588- 1679) justifies his biblical exegesis pointing out, before all, that the Sacred Scriptures “are the outworks of the enemy, from whence they impugn the civil power”. Through the separated essences’ or immaterial substances’ doctrines, which deceiving philosophers say that are proclaimed in the Scriptures, the human race is conducted to harm the original pact that ensures the civil obedience to their respective sovereignty in a superstitious way. However, this is not the consequence drawn from the “Malmesbury’s monster” ambition in training the revelated word of God, and religion in general, to enforce the claims of a secular and mundane State. Both his political philosophy and his philosophia prima are guided by his radical reduction of the reality into moving bodies. His entire exegetical exercise sits on the equalization of all substances as bodies, which does not spare even the ineffable Creator.
Exegesis, corporeality and mortality on Thomas Hobbes' Leviathan
Keywords: Exegese; Materialismo; Ontologia; Mortalidade; Exegesis; Materialism; Ontology; Mortality; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA